Thalassemia-associated osteoporosis: a systematic review on treatment and brief overview of the disease. Issue 12 (December 2016) - Dede, A.; Trovas, G.; Chronopoulos, E.; Triantafyllopoulos, I.; Dontas, I.; Papaioannou, N.; Tournis, S.
Abstract Summary Thalassemia-associated osteoporosis constitutes a major complication in patients with thalassemia. This review presents the existing studies on the treatment of thalassemia-associated osteoporosis and discusses the management of this debilitating complication. A brief presentation of the disease characteristics and pathogenetic mechanisms is also provided. The life expectancy of patients with thalassemia has increased markedly in recent years resulting in the aging of the population and the emergence of new comorbidities. The majority of patients with thalassemia have low bone mineral density and experience lifelong fracture rates as high as 71 %. The pathogenesis of thalassemia-associated osteoporosis (TAO) is multifactorial with anemia and iron overload playing crucial role in its development. Data concerning the prevention and treatment of TAO are extremely limited. We performed a literature research in Pubmed and Scopus to identify interventional studies evaluating the effects of various agents on TAO. Seventeen studies were retrieved. We present the results of these studies as well as a brief overview of TAO including presentation, pathogenesis, and management. Most of the studies identified are of poor quality, are not randomized controlled, and include small number of participants. There are no data concerning effects on fracture rates. Bisphosphonates are the most widely studied agents and among them zoledronic acid is the most well studied. Hormone replacement treatment (HRT) shows beneficial but small effects. Denosumab and strontium ranelate have each been evaluated in only a single study, while there are no data about the effects of anabolic agents. Given the increased life expectancy and the increase in fracture rates with age, more data about the management of TAO are warranted. Moreover, due to the need for lifelong management starting at young age, careful treatment plans which may include sequential treatment may often be required. However, currently, there are no relevant data available.